“Lock and Protect”: Development of a Digital Decision Aid to Support Lethal Means Counseling in Parents of Suicidal Youth - Asarnow, Joan R.; Zullo, Lucas; Ernestus, Stephanie M.; Venables, Chase W.; Goldston, David B.; Tunno, Angela M.; Betz, Marian E. (Frontiers in Psychiatry, 2021)
Objective: Reducing access to lethal methods is an effective suicide prevention strategy, that is often neglected in routine care. Digital interventions have shown promise for addressing such gaps in care and decision aids have proven useful for supporting complicated health-related decisions, like those involving lethal means restriction. This article describes a parent/caregiver-facing web-based decision aid, our development process, and user testing. Method: A user-centered, participatory, mixed methods development design was employed. Beginning with an adult-focused decision aid developed by members of our team, we assessed ten iterations of the parent/caregiver decision aid with stakeholders (N=85) using qualitative interviews and quantitative surveys. Stakeholders included: parents/caregivers whose children had histories of suicidal episodes before age 25; young adults with histories of suicidality; firearm owners/representatives from firearm stores/groups; health/mental health providers; emergency responders; and leaders in youth suicide prevention. Results: The final “Lock and Protect” decision aid had high user acceptability: 100% of participants rated the tool as “useful for changing access to lethal means;" 94% rated the information on the importance of restricting access to lethal means as good to excellent; and 91% rated the information on storage options as good to excellent. Qualitative feedback underscored a preference for offering this digital tool with a “human touch,” as part of safety and discharge planning. Conclusions: “Lock and Protect” is a user-friendly web-based tool with potential for improving rates of lethal means counseling for parents/caregivers of suicidal youth and ultimately reducing premature deaths by suicide.